(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
This article examines the early medieval herding cultures of the Middle Syrdarya region, focusing on their economic practices, social organization, and cultural interactions. It highlights the significance of livestock management, trade networks, and social structures within these communities. Through the analysis of archaeological evidence and historical records, the study provides insights into how these herders adapted to their environment and engaged with neighboring settled societies, contributing to the broader understanding of regional historical dynamics.